Effect of Job Environment on Pulmonary Functions of Railway Employees - Abdul Ghani Waseem, Kaleem Ullah Toori, Mohammad Iqbal, Asim Zulfiqar, Sharif-uz-Zaman (Journal of Rawalpindi Medical College, 2009)
Background: To seek relationship between job related exposure of Pakistan Railways workers and the development of respiratory diseases. Methods: One hundred (100) exposed railway workers and a reference group of 100 office workers were recruited in the study. Respiratory symptoms, smoking habits, physical examination findings, chest x-ray and spirometry results were recorded on standard proforma. Results: The FEV1/FVC ratio was significantly lower in the Railway workers than in the reference group (p<0.001). Exposed Railway employees had significantly high (p<0.001) incidence of pulmonary diseases as compared to the reference group. Disproportionately higher incidence of chronic obstructive airway disease was observed in the exposed Railway employees who smoked as compared to the non-smokers in the same group (p<0.001). Conclusion: In exposed Railway workers there is an increased risk of respiratory symptoms, decline in lung functions and chronic obstructive pulmonary disease (COPD) as compared to referents. There is disproportionately higher incidence of COPD among the smokers in the Railway workers as compared to the non-smokers in the same group.